KOORDINASI RELE ARUS LEBIH DI GARDU INDUK BUKIT SIGUNTANG DENGAN SIMULASI (ETAP 6.00) - Kasmir, Kasmir (JURNAL MEDIA TEKNIK, 2011)
ABSTRACTOne cause of the rise in short circuit current is a disorder that makes the current exceeds the maximum value of the conductor or other electrical equipment. The use of a simple over current relay and reliability in operation, has made the over current relay is widely used. This study aims to find out how the calculation of current and time settings on over current relay and will create a simulation of the coordination of over current relay with a simulator program. The simulator is the ETAP software version 6.0, the software is working to design a network setting values must be entered in advance in accordance with the actual state of the input values are then simulated setting that has been entered in accordance with the procedure. From the simulation results can be concluded that the use of ETAP 6.0 program is very effective to determine the relay coordination in detecting problems and protect them.Keywords : Coordination relay and Simulation Program Flow Over ETAP 6.0